Distribution and Temporal Trends From 1993 to 2015 of Ischemic Stroke Subtypes: A Systematic Review and Meta-Analysis. Issue 4 (April 2018) - Ornello, Raffaele; Degan, Diana; Tiseo, Cindy; Di Carmine, Caterina; Perciballi, Laura; Pistoia, Francesca; Carolei, Antonio; Sacco, Simona
Abstract : Background and Purpose—: Preventive strategies, together with demographic and socioeconomic changes, might have modified the worldwide distribution of ischemic stroke (IS) subtypes. We investigated those changes by means of a systematic review and meta-analysis. Methods—: We evaluated all population- and hospital-based studies reporting the distribution of IS etiologic subtypes according to the TOAST criteria (Trial of ORG 10172 in Acute Stroke Treatment). Studies were identified by searching articles indexed on PubMed and Scopus from January 1, 1993, to June 30, 2017. Two independent investigators extracted data and checked them for accuracy. Proportions of each etiologic subtype were pooled according to a random effect meta-analytic model weighted by study size; temporal trends were assessed using a mixed-effect meta-regression model. Results—: Sixty-five studies including patients from 1993 to 2015 were finally included. Overall, ISs were attributed to cardioembolism (22%; 95% confidence interval [CI], 20–23); large artery atherosclerosis (23%; 95% CI, 21–25); small artery occlusion (22%; 95% CI, 21–24); other determined cause (3%; 95% CI, 3–3); and undetermined cause (26%; 95% CI, 24–28). Cardioembolism was the leading IS etiologic subtype in whites (28%; 95% CI, 26–29) and large artery atherosclerosis in Asians (33%; 95% CI, 31–36). Meta-regression showed an increasing temporal trend for cardioembolism in whites (2.4% annually, P =0.008) and large artery atherosclerosis in Asians (5.7% annually, P <0.001), and a decrease for small artery occlusion in whites (−4.7% annually, P =0.001); there was considerable heterogeneity across all the analyses. Conclusions—: According to our systematic review and meta-analysis, cardioembolism in whites and large artery atherosclerosis in Asians are the leading causes of IS. The heterogeneous distribution of etiologic subtypes of IS may depend on the demographic and socioeconomic characteristics of the different populations. More extensive protocols should be adopted to reduce the persistently relevant proportion of undetermined cause IS. Abstract : Supplemental Digital Content is available in the text.